'Chicha' (Corn Beer) Consumption and Production in the Quebrada de Humahuaca, Jujuy, Argentina in Pre-Inka Times (1250–1450 AD) - Leibowicz, Iván (Archaeology of Food and Foodways, 2025)
This research explores the production of chicha (corn beer) in the Andes of northwestern Argentina through various interdisciplinary approaches, including materiality analysis, ethnographic work, and comparison with other Andean contexts. The site of Juella, comprising 420 enclosures spread over 6 ha2 in the Quebrada de Humahuaca, Jujuy, is the focal point of this study. Occupations at Juella are limited to the Late Intermediate Period (1250–1450 AD).During this period, new societies emerged from the aggregation of smaller, dispersed communities into new spaces. Chicha held significant cultural and social importance in these emerging societies, contributing to ethnic identities, annual celebrations, and various rites and rituals among Andean cultures. Beyond its role in cultural practices, chicha played a crucial role in fostering social and cultural cohesion within and among communities. In this case, rather than accentuating social differences, chicha facilitated shared life experiences and the formation of communal identity.